ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНДА ЭКОНОМИКАЛЫҚ РЕФОРМАЛАРДЫҢ БАСЛАНЫЎ ҲӘМ ЖӘМИЙЕТЛИК-ЭКОНОМИКАЛЫҚ ДҮЗИЛИСТИҢ ӨЗГЕРИЎИ - Сарыбаев, А.К. (FAN va JAMIYAT, 2023)
This article shows the difficult socio-economic situation of the Republic of Karakalpakstan in the initial period of transition to a market economy. The processes of the emergence of an economic management system and the formation of a market infrastructure in the national economy of the region in the course of economic reforms are reflected. It also highlights measures to change the form of ownership and the development of small business and entrepreneurship.